Comparison of Dipper and Non-Dipper Hypertension Patterns According to Chronic Kidney Disease Stage - Turan Erkek Esra; Akin Seydahmet; Ozgur Yasemin; Aydin Zeki; Bicik Zerrin (Journal of Nephrology Advances, 2019)
Introduction Hypertension is a major cardiovascular risk factor. There is a strong relationship between blood pressure (BP) elevation and stroke, myocardial infarction, heart failure and mortality due to kidney disease. It is known that the loss of the dipping pattern in hypertension is associated with increased target organ damage. In our study, we aimed to investigate the prevalence of dipper hypertension (DHT) and nondipper hypertension (NDHT) and related factors in patients with stage 1 and 2 chronic kidney disease (CKD). Materials and Methods A total of 158 patients diagnosed with stage 1 or stage 2 CKD were included in the study. Demographic characteristics, anthropometric measurements, physical examination findings and laboratory results of the patients were recorded. Ambulatory BP monitoring was performed in all patients. Results Of the 158 patients (female n: 98), 78 (49%) were in the stage 1 CKD group and 80 (51%) were in the stage 2 CKD group. No significant difference was observed in the prevalence of DHT or NDHT between hypertensive patients in the stage 1 and 2 CKD groups. The rate of NDHT was 59.5% (94/158 patients). Female patients had more DHT in the general population and in the stage 1 group than male patients (p=0.05, p=0.01, respectively). Conclusion No significant difference was observed in the prevalence of DHT or NDHT between hypertensive patients in the stage 1 and 2 CKD groups. The prevalence of DHT in female patients was significantly higher in both groups than in men in both groups, but especially in the stage 1 CKD group.
Keywords: Hypertension